Perioperative Beta-Blocker for Atrial Fibrillation after Cardiac Surgery: A Meta-Analysis - Kim, Sue Hyun; Jang, Myoung-jin; Hwang, Ho Young (The Thoracic and Cardiovascular Surgeon, 2020)
Background This meta-analysis was conducted to evaluate the impact of perioperative use of beta-blocker (BB) on postoperative atrial fibrillation (POAF) after cardiac surgery other than isolated coronary artery bypass grafting (CABG).Methods Five online databases were searched. Studies were included if they (1) enrolled patients who underwent cardiac surgery other than isolated CABG and (2) demonstrated the impact of perioperative use of BB on POAF based on the randomized controlled trial or adjusted analysis. The primary outcome was the occurrence rates of POAF after cardiac surgery. A meta-regression and subgroup analysis were performed according to the proportion of patients with cardiac surgery other than isolated CABG and the timing of BB use, respectively.Results Thirteen articles (5 randomized and 8 nonrandomized studies: n = 25,496) were selected. Proportion of enrolled patients undergoing cardiac surgery other than isolated CABG ranged from 7 to 100%. The BBs were used in preoperative, postoperative, and both periods in 5, 5, and 3 studies, respectively. The pooled analyses showed that the risk of POAF was significantly lower in patients with perioperative BB than those without (odds ratio, 95% confidence interval = 0.56, 0.35–0.91 and 0.70, 0.55–0.91 in randomized and nonrandomized studies, respectively). The risk of POAF was lower in the BB group irrespective of the proportion of nonisolated CABG. Benefit regarding in-hospital mortality was inconclusive. Perioperative stroke and length of stay were not significantly different between BB and non-BB groups.Conclusions Perioperative use of BB is effective in preventing POAF even in patients undergoing cardiac surgery other than isolated CABG, although it did not translate into improved clinical outcomes.
Keywords: statistics; surgery; complications; cardiac